Analysis of Correspondence Capabilities of Personnel Staff of Military Resort Command 044/Garuda Dempo - Ayu Puspita Indah Sari; Rahmi Fadilla (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Effective correspondence is essential for clear and professional communication, particularly in administrative settings. This study investigates the correspondence abilities of personnel staff at Military Resort Command 044/Garuda Dempo, focusing on common language errors and strategies for improvement. Using a qualitative method with a descriptive approach, the research analyzed official letters and conducted interviews to gather comprehensive insights. The findings reveal that staff proficiency in correspondence is low, marked by frequent deviations from standard formats and ineffective sentence structures. These deficiencies are primarily attributed to a lack of formal training in official letter writing. To address these issues, the study recommends implementing targeted training programs, providing constructive feedback, using exemplary models of correspondence, conducting regular writing exercises, and leveraging supportive tools. These interventions aim to enhance the staff’s ability to produce clear and effective official communication